Clinical Outcomes of Children Diagnosed Dengue-Associated Acute Liver Failure with or without N-Acetylcysteine Treatment: A Retrospective Cohort Study. (7th June 2021) - Sriphongphankul, Hansa; Liabsuetrakul, Tippawan; Osatakul, Seksit
Abstract: Objectives: N-acetylcysteine (NAC) has been shown to prevent hepatic damage and improve microcirculatory blood flow and oxygen delivery to the tissue. Previous studies have proposed the benefit of NAC in dengue-associated acute liver failure (ALF). However, most studies are descriptive and lack comparison between groups. We aimed to compare the ALF resolution rate and mortality rate of those who received and did not receive NAC treatment. Methods: A retrospective cohort study was conducted among children aged <15 years who were diagnosed with dengue-associated ALF at a tertiary hospital in Thailand, between January 2002 and July 2019. Demographic and clinical information were collected. Main outcomes were ALF resolution and mortality rate. Results: Thirty-three patients were included of which 16 received NAC treatment (48.5%). Mean ages were 8.5 years (SD 3.7) and mean onset of ALF was 6.3 days (SD 1.6) after onset of fever. The grading of hepatic encephalopathy (HE) and organ failure was not significantly different between the two groups. In the NAC group, 13/16 children were prescribed 100 mg/kg/day of NAC until INR <2 without HE or <1.5 with HE. NAC was initiated 1.1 days (SD 0.3) after the ALF diagnosis. The NAC group showed a higher rate of ALF resolution (75% vs. 53% in the non-NAC group, p = 0.34) with a lower mortality rate (31% vs. 53%, p = 0.36). Side effects of NAC were not found. Conclusion: NAC may be beneficial in dengue-associated pediatric ALF. Further well-designed randomized control trials should be carried out.